Changes of glutathione S-transferase activities and gene expression in Triticum aestivum during polyethylene-glycol induced osmotic stress - Gallé, Ágnes (Acta Biologica Szegediensis, 2005)
Glutathione S-transferase (GST) isoenzymes represent a large and variable group of antioxidative enzymes, with several different activities and sequence patterns. The GST activities of drought-tolerant Triticum aestivum L. cv. Kobomugi and cv. Plainsman were measured after one week 400 mOsm polyethylene glycol (PEG) treatment. The GST activities were much higher in the root than in the shoot and were induced by PEG especially in root. The aim of our work was to sort out the drought stress related wheat GST genes. Phylogenetic analysis of wheat GSTs was performed in silico and using the tentative consensus sequences a dendogram was composed. According to the conserved sequences used for classification of GST proteins, we could identify six groups of wheat GSTs. The phi GSTs are the most heterologous group, containing 25 sequences. The zeta, theta and tau GSTs are represented by 10, 9 and 8 TCs respectively. There are two other unidentified groups containing 8 and 6 sequences. Homology found between the osmotic stress upregulated sequences and the GST coding TCs were identified.